Purulent Bacterial Pericarditis - Emily S. Lee, MD; Charlie Lin, MD; Jena Pizula, MD; Kruti A. Pandya, MD; Anilkumar O. Mehra, MD; Helga Van Herle, MD (JACC: Case Reports, 2024)
Bacterial pericarditis is a rare phenomenon that progresses rapidly and carries high mortality. Patients presenting with new pericardial effusions are often evaluated for concomitant rheumatologic, oncologic, and infectious diseases. We present a complex case of purulent pericarditis with pneumopericardium.